1997
DOI: 10.1073/pnas.94.1.292
|View full text |Cite
|
Sign up to set email alerts
|

Newborn primate infants are entrained by low intensity lighting

Abstract: At the present time we do not know when the circadian timing system of human infants becomes responsive to light. Because of human study limitations, it is not currently possible to address this issue in clinical studies. Therefore, to provide insights into when the circadian system of humans becomes responsive to light, baboons were studied. We first assessed if the biological clock located in suprachiasmatic nuclei (SCN) is responsive to light at birth. When term newborn infants were exposed to bright light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…However, there are very few relevant studies on maturation in primates, either human or nonhuman (4,5). The few recent nonhuman primate neonatal studies that exist relate only to the responsiveness of these rhythms to light (6,7).…”
mentioning
confidence: 99%
“…However, there are very few relevant studies on maturation in primates, either human or nonhuman (4,5). The few recent nonhuman primate neonatal studies that exist relate only to the responsiveness of these rhythms to light (6,7).…”
mentioning
confidence: 99%
“…Light entrainment of circadian rhythms has been demonstrated in animals. 407,408 Studies in newborn infants as early as 28 weeks gestation have demonstrated some aspects of circadian rhythmicity in body temperature, 401,[409][410][411][412] respiratory pause frequency 411 and blood amino-acid level measurements. 413 Using amplitude integrated EEG, cyclic changes in sleep state have been identified in preterm infants as early as 27 weeks gestation, with onset at 6 days of age.…”
Section: To 32 Weeks Gestational Age and Beyondmentioning
confidence: 99%
“…Tissue sections adjacent to those used for DG studies were used. In situ hybridization for c-fos,per1 mRNA were performed by using methods similar to those described (16). The Riboprobe system (Promega) was used to…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the SCN of term baboon infants (gestation length 180-185 days) are responsive to light at birth and that photic responsiveness is retina-mediated (16). To address when the developing primate circadian system first becomes responsive to light, we studied progressively younger preterm baboon infants.…”
Section: Photic Responsiveness Of the Scn In Preterm Infantsmentioning
confidence: 99%
See 1 more Smart Citation